Harga Diri Pada Orang Dengan Hiv/Aids (Odha) Di Violet Community Yogyakarta (Studi Kasus) - Pramesti, Despita (Jurnal Kesehatan Masyarakat, 2014)
Background: Source of stress which resulted in people with HIV/AIDS (ODHA) is the high rate of death caused by this disease and especially societys view of people with HI AIDS (ODHA) so this will affect the self- esteem of people with HIV/AIDS (ODHA) . Objective: Observe the description of self-esteem of people with HIV/AIDS(ODHA) and the factors that affect the self-esteem of people with HIV/AIDS(ODHA) in Yogyakarta community Violet. Methods: The use of non-experimental research exploratory descriptive study design with qualitative methods. Type the sampling is purposive sampling by taking a subject of study of people with HIV/AIDSin the Community Violet Yogyakarta about 20 people. 5 ODHA taken as respondents. Conclution: The results of this study indicate that the picture self-esteem of people with HIV/AIDS(ODHA) in the criteria feeling accepted, respected and competent 5 respondents indicated a high level of self-esteem. And the feeling of valuable criteria 1 respondent indicated a high level of self-esteem and 4 respondents indicated a low level of self-esteem. Factors affecting the formation of self-esteem of people with HIV/AIDS(ODHA) in Violet community due to the conditions of acceptance of the individual as well as the advantages and disadvantages of himself, success, respect from others, the support of fellow sufferers of HIV / AIDS, and support from the community.